Analisis Stabilitas Lereng Pembangunan Embung Bena dengan Geostudio - Antjak, Antonius L.; Lasmana, Lasmana; Sayonara, Ramzy; Nope, Fabianus J. S. (Jurnal Kridatama Sains dan Teknologi, 2025)
The Bena Reservoir was designed as a water supply solution in Bena Village, South Central Timor District, which has semi-arid climatic conditions. The success of embankment construction is not only determined by the storage capacity, but also the slope stability of the embankment body which affects the safety and successful functioning of the embankment. This research focuses on analyzing slope stability using GeoStudio 2012 software and the Modified Morgenstern method. The analysis was conducted under four operating conditions: empty, normal water level, flood water level, and rapid drawdown. Geotechnical parameters such as cohesion, inner shear angle, and soil permeability were included in the simulation. Results showed that the Safety Factor (SF) values under all conditions were well above the minimum required (SF > 1.2 - 1.5), with the highest value being 43.525 and the lowest being 10.122. This finding confirms that the embankment slopes are in a very stable condition. Therefore, The Bena Reservoir technically meets the slope safety criteria and is ready to support safe and sustainable water management